1989
DOI: 10.1002/ijc.2910430110
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 dna in cervical cancers and in lymph nodes of cervical cancer patients: A diagnostic marker for early metastases?

Abstract: Human papillomavirus (HPV) 16 is most prevalent in cervical cancers and also persists in metastases. We examined HPV16-DNA-positive primary cancers and several lymph nodes from each of 14 patients to evaluate the use of HPV16 DNA as a diagnostic marker for the detection of early node involvement. The HPV16 DNA was exclusively integrated in 39% of the primary cancers, predominantly episomal in 36%, and integrated and extrachromosomal to a similar extent in 25%. Thirteen of 16 involved lymph nodes contained HPV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 21 publications
10
55
0
2
Order By: Relevance
“…Recently, similar data have emerged with respect to HPV-16-containing cervical carcinomas, a proportion of which have been found to contain episomal HPV DNA only (Fuchs et al, 1989;Matsukura et al, 1989;Cullen et al, 1991). Furthermore, Nasseri et al (1991) have found that the presence of HPV-16 E2-encoding transcripts does not affect the expression levels of the E7 protein in immortalized cervical keratinocytes suggesting that E2 interruption triggered by integration is not causally related to increased E7 expression.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, similar data have emerged with respect to HPV-16-containing cervical carcinomas, a proportion of which have been found to contain episomal HPV DNA only (Fuchs et al, 1989;Matsukura et al, 1989;Cullen et al, 1991). Furthermore, Nasseri et al (1991) have found that the presence of HPV-16 E2-encoding transcripts does not affect the expression levels of the E7 protein in immortalized cervical keratinocytes suggesting that E2 interruption triggered by integration is not causally related to increased E7 expression.…”
Section: Discussionmentioning
confidence: 66%
“…However, this feature is not universal, and an estimated 30% of cervical cancers do not contain integrated HPV DNA (18,35). Highgrade lesions and cancers could be screened for E2 expression before a decision were made on whether E2 immunotherapy was appropriate, much as breast cancers are now screened for expression of the HER2/neu protein before Herceptin (trastuzamab; Genentech, San Francisco, Calif.) therapy is chosen (24,46).…”
Section: Discussionmentioning
confidence: 99%
“…However, Cullen et al observed pure integrated HPV DNA, mixed forms and episomal forms in HPV 16 containing cancers, whereas all HPV 18 containing cancers revealed only integrated form (26); Matsukura et al detected exclusive episomal forms of HPV 16 DNA in infected cervical epithelium, albeit this form was present in 70% of investigated cervical malignancies (27)(28)(29).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%